(untitled) (Conferencea, 2024)
Diversification of the portfolio is important for investors to maximize their investment benefits and reduce risks. By portfolio diversification, we understand that investors simultaneously invest in various securities (shares, bonds, short-term assets, long-term assets) and other similar financial assets. Nevertheless, portfolio diversification is not aimed at increasing the expected income from them, but at reducing possible risks and dangers. In our research, we consider 4 main components of portfolio diversification.